ANALISIS KONDISI MINYAK TRANSFORMATOR DENGAN UJI DISSOLVED GAS ANALYSIS (DGA) DAN BREAKDOWN VOLTAGE PADA PT PLN NUSANTARA POWER UP MUARA KARANG - Badriyah, Intan Layla; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
Transformer oil is one of the important components in a transformer. In transformers, oil functions as an insulating material andalso acts as a coolant. Transformer oil will have loads in the form of electric fields and thermal loads when the transformer isoperating. The load on the oil causes the temperature of the oil to increase, so that the value of the breakdown voltage decreases and the quality of the oil decreases. Apart from that, this load also causes gases to be contained in the oil. The presence of gases in transformer oil indicates that there is an indication of interference which will result in a decrease in the quality of the insulation. A decrease in insulation quality can cause transformer failure. In this research, the tests carried out were the Dissolved Gas Analysis (DGA) test to determine the gas contents and the Breakdown Voltage test for the breakdown voltage value. Tests on transformer oil were carried out at PT PLN Nusantara Power UP Muara Karang. The results of the research show that based on DGA testing, the faulty transformer has indications of thermal disturbances accompanied by electric arc splitting and damage to the paper insulation, while active transformers have indications of thermal disturbances accompanied by damage to the paper insulation. Based on the breakdown voltage test, the faulty transformer and the active transformer are in normal condition because they are below the standard value (40 kV/2.5 mm). Keywords: Transformer oil, insulation quality, gas content, breakdown voltage